2015
DOI: 10.1097/qad.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose tissue as a reservoir for memory CD4+ T cells and HIV

Abstract: Objective To determine whether adipose tissue functions as a reservoir for HIV-1. Design We examined memory CD4 T cells and HIV DNA in adipose tissue-stromal-vascular-fraction (AT-SVF) of 5 patients (4 ART-treated and 1 untreated). To determine if adipocytes stimulate CD4 T cells and regulate HIV production, primary human adipose cells were co-cultured with HIV-infected CD4 T cells. Methods AT-SVF T cells were studied by flow cytometry, and AT-SVF HIV DNA (Gag and Env) was examined by nested PCR and sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 38 publications
10
124
1
Order By: Relevance
“…The results presented here demonstrate that adipocytes have significant impact on ART distribution and activity within AT, which is newly believed to constitute a reservoir for latently infected HIV-/SIV-infected CD4 T cells (Couturier et al, 2015; Damouche et al, 2015; Couturier et al, 2016; Damouche et al, 2017; Hsu et al, 2017; Koethe et al, 2017; Couturier et al, 2018). In particular, these data suggest that adipocytes markedly diminish the antiretroviral effectiveness of NRTIs, particularly tenofovir, which constitutes an important “backbone” component of many antiretroviral regimens and is a first line agent for the treatment of HIV infection.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The results presented here demonstrate that adipocytes have significant impact on ART distribution and activity within AT, which is newly believed to constitute a reservoir for latently infected HIV-/SIV-infected CD4 T cells (Couturier et al, 2015; Damouche et al, 2015; Couturier et al, 2016; Damouche et al, 2017; Hsu et al, 2017; Koethe et al, 2017; Couturier et al, 2018). In particular, these data suggest that adipocytes markedly diminish the antiretroviral effectiveness of NRTIs, particularly tenofovir, which constitutes an important “backbone” component of many antiretroviral regimens and is a first line agent for the treatment of HIV infection.…”
Section: Discussionmentioning
confidence: 65%
“…They observed that NNRTI concentrations were significantly higher in AT lysates compared to PI concentrations, whereas N(t)RTIs were undetectable. Others and we have recently demonstrated that latently-infected CD4 T cells accumulate in AT and establish replication-competent reservoirs during chronic HIV infection, indicating the need for better understanding of antiretroviral pharmacology in AT (Couturier et al, 2015; Damouche et al, 2015; Couturier et al, 2016; Damouche et al, 2017; Hsu et al, 2017; Koethe et al, 2017; Couturier et al, 2018). …”
Section: Introductionmentioning
confidence: 91%
“…Recently, adipose tissue, and particularly memory CD4 T cells in this tissue, has been identified as a potentially important HIV reservoir, with the detection of total viral DNA in untreated macaques but also in patients on effective treatment (176,177). This reservoir is inducible by ex vivo activation.…”
Section: Other Tissues and Fluidsmentioning
confidence: 99%
“…Consequently, adipose tissue has been suggested to be a reservoir for specific infectious agents. [12][13][14][15] Human cytomegalovirus (HCMV), a member of the b-herpesvirus family, is one of the most common viruses infecting adults, with the seropositive rate ranging from 60-99% globally. 16 It typically presents as an asymptomatic infection in healthy individuals but can be life-threatening in immunocompromised individuals such as organ and bone marrow transplant patients or individuals positive for HIV/ AIDS.…”
Section: Introductionmentioning
confidence: 99%